Dye adsorption on layered graphite oxide - Bradder, Philip; Ling, Sie King; Wang, Shaobin; Liu, Shaomin (American Chemical Society, 2011)
Graphite oxide (GO) was prepared by a modified Hummers−Offeman method and was tested as an adsorbent for the removal of dyes in aqueous solution. The structure of GO was characterized by N2 adsorption, X-ray diffraction (XRD), and Fourier transform infrared (FT-IR) spectroscopy. It is found that GO does not show a significant change in surface area, but the layered graphene structure was expanded, and several surface oxygen functional groups were formed, which play a significant role in adsorption. The amount of the dyes, methylene blue and malachite green, adsorbed on the GO was much higher than that on graphite, and the adsorption capacity based on the Langmuir isotherm is (351 and 248) mg·g−1, respectively, much higher than activated carbon. The adsorption mechanism was proposed as electrostatic attraction.